The puzzle of non-participation in continuing training: an empirical study of chronic vs. temporary non-participation - Uschi Backes-Gellner; Johannes Mure; Simone N. Tuor (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
Although participation in continuing vocational training is often found to be associated with considerable individual benefits, a puzzlingly large number of people still do not take part in training. In order to solve the puzzle we distinguish between temporary and chronic non-participants. Previous studies have shown that training participants and non-participants differ in unobservable characteristics and therefore self-select into training or not. We show that even non-participants cannot be treated as a homogeneous group: there are those who never take part in training (chronic non-participants) and those who are not currently taking part (temporary (non-)participants). Using a unique data set of non-participants commissioned by the German 'Expert Commission on Financing Lifelong Learning' and covering a very large number of individuals not taking part in training, we separate and compare chronic and temporary non-participants. By estimating a sample selection model using maximum likelihood estimation we take potential selection effects into account: temporary (non-)participants may be more motivated or may have different inherent skills than chronic nonparticipants. We find that chronic non-participants would have higher costs than temporary (non-)participants and their short-term benefits associated with their current jobs would be lower. However, in the long run even chronic non-participants would benefit similarly from participation due to improved prospects on the labor market. The results indicate that chronic non-participants either misperceive future developments or suffer from an exceptionally high discount rate, which in turn leads in their view to a negative cost-benefit ratio for training.
Keywords: 330; Weiterbildung; Teilnehmer; Bildungsbeteiligung; Bildungsinvestitionen; Bildungsertrag; Kosten-Nutzen-Analyse; Bildungsökonomie